Sulfate attack on concrete - Skalny, Jan (Modern concrete technology series, 2002)
Sulfate attack is one of several mechanisms of concrete deterioration. This book provides a comprehensive reference to this subject, covering: a short history of concrete deterioration due to sulfate attack, the origin of sulfates in concrete, the importance of appropriate concrete processing, forms and physical-chemical mechanisms of concrete deterioration due to sulfates, preventative measures, standardization and numerous case histories.